2022
DOI: 10.1002/pssr.202200040
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Effective Area of Small‐Sized CIGS Modules by Printed Ag Front Contacts

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/pssr.202200040.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…[5,[11][12][13][14][15] In previous studies, the potential of parallel dispensing technique has been demonstrated for hightemperature curing pastes as well as for low-temperature curing pastes. [5,16,17] During the dispensing process, a highly filled suspension is forced through nanometer-sized nozzles and filament threads or rather paste threads occur. These paste threads get in DOI: 10.1002/adem.202300010…”
Section: Introductionmentioning
confidence: 99%
“…[5,[11][12][13][14][15] In previous studies, the potential of parallel dispensing technique has been demonstrated for hightemperature curing pastes as well as for low-temperature curing pastes. [5,16,17] During the dispensing process, a highly filled suspension is forced through nanometer-sized nozzles and filament threads or rather paste threads occur. These paste threads get in DOI: 10.1002/adem.202300010…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Here, the electrodes are also applied onto TCO layers and orientated perpendicular to the P1P2P3 interconnections. The architecture of this thin-film concept, 23,24 its unique features, 25 and its industrial manufacturing processes 26,27 are illustrated in the literature. It should be mentioned that front contacts on CIGS substrates are not as common as on silicon solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The electrodes are applied by flatbed screen printing and parallel dispensing. 23 Nevertheless, published results show the limitation of front contact metallization of CIGS modules. Nowadays, curing temperatures of T c ≈ 200 C are used to obtain the contact formation between printed electrodes and TCO layers, especially indium tin oxide (ITO) layers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations